The metabolic recovery of marathon runners: an untargeted 1H-NMR metabolomics perspective - Bester, Rachelle; Stander, Zinandré; Mason, Shayne; Keane, Karen M.; Howatson, Glyn; Clifford, Tom; Stevenson, Emma J.; Loots, Du Toit (Frontiers in Physiology, 2023)
eExtreme endurance events may result in numerous adverse metabolic, immunologic, and physiological perturbations that. In turn, these may not only diminish athletic performance and adversely affect, but also impact the overall health status of the an athlete, especially in the absence of sufficient recovery. A comprehensive understanding of the post-marathon recovering metabolome, may aid in the identification of new biomarkers associated with marathon-induced stress, recovery, and adaptation, which can facilitate the development of improved training and recovery programs and personalized monitoring of athletic health/recovery/performance. Nevertheless, an untargeted, multi-disciplinary elucidation of the complex underlying biochemical mechanisms involved in recovery after such an endurance event is yet to be demonstrated. Considering this, the current investigation employed an untargeted proton nuclear magnetic resonance1H-NMR metabolomics approach to characterize the post-marathon recovering metabolome by systematically comparing the pre-, immediately post, 24 h, and 48 h post-marathon serum metabolite profiles of 15 athletes. A total of 26 metabolites were identified to fluctuate significantly among post-marathon and recovery time points and were mainly attributed to the recovery of adenosine triphosphateATP, redox balance and glycogen stores, amino acid oxidation, changes to gut microbiota, and energy drink consumption during the post-marathon recovery phase. Additionally, metabolites associated with delayed-onset muscle soreness were observed; however, the mechanisms underlying this commonly reported phenomenon remain to be elucidated. Although complete metabolic recovery of the energy-producing pathways and fuel substrate stores was attained within the 48 h recovery period, several metabolites remained perturbed throughout the 48 hour recovery period and/or fluctuated again following their initial recovery to pre-marathon-related levels.